2011
DOI: 10.1590/s0037-86822011005000013
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of hantavirus infection in humans in the border region between Brazil and Argentina

Abstract: Introduction: According to reports by the Ministry of Health, in the far western region of the State of Santa Catarina, there have been no reports of hantavirus pulmonary syndrome, a zoonotic disease transmitted by feces of infected rodents. A seroepidemiological study of residents of this region, was conducted, with the aim of determining the presence of hantavirus infections. A total of 340 volunteers of both genus, from the towns of Belmonte and Paraíso, were studied. Methods: The serum of these patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
2
9
1
1
Order By: Relevance
“…These antibody levels are similar to those reported in other South American studies using IgG-ELISA where seropositivity ranged from 0.2% to 14.3% 2,6,12,18,24,25,27 . Therefore, hantavirus infections are probably occurring in the studied municipalities despite of no HCPS reported cases.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…These antibody levels are similar to those reported in other South American studies using IgG-ELISA where seropositivity ranged from 0.2% to 14.3% 2,6,12,18,24,25,27 . Therefore, hantavirus infections are probably occurring in the studied municipalities despite of no HCPS reported cases.…”
supporting
confidence: 89%
“…Currently, two known strains circulate in the state: Juquitiba associated to Oligoryzomys nigripes and Jabora related to Akodon montensis 21,28 . Although, HCPS cases were not reported in the west of the state of Santa Catarina, a previous study in this region showed individuals previously infected by hantavirus in two municipalities 27 . Thus, this work has been done in order to obtain better information on antibody levels to hantavirus in the west of the state Santa Catarina, at the border with northern Argentina.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In another study conducted in cities near the border between Brazil and Argentina, still in the State of Santa Catarina, they found a 3.5% seroprevalence 11 . The highest reported level of infection with an index of 4.7% was found in the City of Cássia dos Coqueiros, located in the State of São Paulo, in the Southeast region 12 .…”
mentioning
confidence: 91%
“…Residents of urban areas also have links to the field, through work or field-related activities which might increase the risk of exposure to rodent reservoirs 11,13 . Thus, when the questionnaire was administered, a majority of the population expressed having experienced situations considered to enhance the risk for hantavirus infection, including rural tourism (74%) and exposure to house cleaning in the countryside, sheds, and other similarities (71%).…”
mentioning
confidence: 99%